Design and Synthesis of Mobile Robot Controller using Fuzzy - Islam, Md. Shabiul; Azim, Md. Anwarul; Jahan, Md. Saukat; Othman, Masuri (IEEE, 2006)
This paper describes a Fuzzy Logic Controller (FLC) algorithm for designing an autonomous mobile robot controller (MRC). The controller enables the robot to navigate in an unstructured environment and that avoid any encountered obstacles without human intervention. The autonomous mobile robot is found to be able to react to the environment appropriately during its navigation to avoid crashing with obstacles by turning to the proper angle while moving. The Fuzzy Logic algorithm has proven a commendable solution in dealing with certain control problems when the situation is ambiguous. One of the main difficulties faced by conventional control systems is the inability to operate in a condition with incomplete and imprecise information. As the complexity of a situation increases, a traditional mathematical model will be difficult if not impossible to implement. Fuzzy Logic is a tool for modeling uncertain systems by facilitating common sense reasoning in decision-making in the absence of complete and precise information. In this paper, the controller of an autonomous mobile robot is designed based on the theories of Fuzzy Logic. The wheeled robot is able to navigate by itself in a completely unstructured environment. The codes of MRC has written for implementing the separate modules of the Fuzzifier, Fuzzy Rule Base, Inference mechanism and Defuzzifier as hardware blocks.